Study on Seepage Laws of Completely Weathered Phyllite Slope Under Rainfall - Liu ChaoQun; Huang XiaoMing; Liu Dan; Zhu LiQing; Sun Yang (E3S Web of Conferences, 2020)
According to the available geological data and monitoring data, the completely weathered phyllite slope dilates and softens under the condition of continuous rainfall, which is then prone to instability failure. The indoor artificial rainfall test was carried out through the construction of the slope model, and the soil moisture sensor, pore water pressure sensor and matric suction sensor were used to study the variation laws of moisture content, pore water pressure and infiltration line at the back edge, slope body and the foot of the slope under continuous heavy rainfall. According to the sensor data and recorded information, with the influence of heavy rainfall over a long period of time, the water content and pore water pressure increased firstly, then decreased, and finally stabilized. The infiltration line moved from the top, the surface and the foot of the slope to the slope body, and shallow slip failure occurred in the shallow layer of the slope body.